Contributions to species of Xylariales in China-3. Collodiscula tubulosa (Xylariaceae) - Xie, Xin; Liu, Li-Li; Shen, Xiang-Chun; Kang, Ying-Qian; Hyde, Kevin D.; Kang, Ji-Chuan; Li, Qi-Rui (Phytotaxa, 2020)
A new Collodiscula, found on a bamboo culms in China, differs from C. japonica, C. fangjingshanensis, C. leigongshanensis, C. bambusae and C. chiangraiensis in having 5-septate ascospores (42.5–65 × 10–15.5 µm). It is described as a new species, Collodiscula tubulosa sp. nov. based on the morphology and molecular phylogeny.